2018
DOI: 10.3390/ijerph15010111
|View full text |Cite
|
Sign up to set email alerts
|

CRP Genotypes Predict Increased Risk to Co-Present with Low Vitamin D and Elevated CRP in a Group of Healthy Black South African Women

Abstract: Low 25-hydroxyvitamin D (25(OH)D) and elevated C-reactive protein (CRP) concentrations are independently associated with adverse health outcomes, including cardiovascular disease (CVD). Although an inverse association between these factors has been described, the underlying mechanisms remain unknown. We postulate that environment–gene interactions, through which 25(OH)D interacts with single nucleotide polymorphisms (SNPs) within the CRP gene, modulate CRP; that certain CRP genotypes predispose individuals to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“… 19 , 20 There is also an accumulating body of evidence supporting biological mechanisms which showed that Black people have a higher NCDs risk, and this is also widely acknowledged for CVD risk, especially in Black women. 21-23 …”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 There is also an accumulating body of evidence supporting biological mechanisms which showed that Black people have a higher NCDs risk, and this is also widely acknowledged for CVD risk, especially in Black women. 21-23 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with vitamin D deficiency have higher levels of C-reactive protein, which may influence the development of cancer and multiple cardiovascular diseases (another explanation for the high prevalence of these pathologies in the Black race). 85 , 86 Additionally, it has been observed that vitamin D deficiency would be related to the development of cardiovascular disease in African American people with type 2 diabetes mellitus. The explanation for this is that vitamin D deficiency would cause downregulation of hydrogen sulfide and cyclic adenosine monophosphate – two crucial signalling molecules related to the prevention of cardiovascular oxidative stress and inflammation.…”
Section: Vitamin D Deficiency/insufficiency In Dark-skinned Peoplementioning
confidence: 99%
“…However, the underlying mechanisms remain to be clarified. One route that has been recognized is that vitamin D affords protection against circulatory diseases by reducing inflammation (9)(10)(11)(12). Lessstudied pathways include improving the blood lipid profile (13), downregulation of the renin-angiotensin system improving blood pressure (14,15), enhancement of insulin secretion and insulin sensitivity (16,17), protection against uncontrolled angiogenesis (18) and influencing blood coagulation (19,20).…”
Section: Introductionmentioning
confidence: 99%